Geographies of Immigration: Samuel Rawet's Rio de Janeiro and Moacyr Scliar's Porto Alegre - Kirschbaum, Saul (Cadernos de Língua e Literatura Hebraica, 2022)
The work of Moacyr Scliar and that of Samuel Rawet have at least one aspect in common. Scliar, born in Porto Alegre and son of immigrants, and Rawet, born in Poland but no less “carioca”, dedicated to their cities – hometown or host – a prominent role, giving them, in their writings, almost the position of characters. Scliar’s A guerra no Bom Fim and O exército de um homem só, and Rawet’s “Reinvenção de Lázaro” and “Madrugada seca”, are eloquent examples of this protagonism. Other authors of Jewish ethnic origin, immigrants or children of immigrants, such as Ronaldo Wrobel in Traduzindo Hannah and Eliezer Levin in Bom Retiro, followed this path. This article seeks to deepen the analysis of the relationship of the chosen authors with their cities of residence, trying to follow the geographical displacements of Jews who immigrated, notably from Eastern Europe, and their concentration in specific neighborhoods.